Open Hearts, Open Minds: Trust, Confidence and Security Building in Northeast Asia. Issue 2 (2nd July 2020) - Miall, Hugh; Shibata, Ria
ABSTRACT: The East Asian peace has lasted since 1979, but regional and global rivalries, unresolved historical grievances, and new nuclear weapons threaten its continuation. In order to reduce these risks, confidence-building measures and crisis management mechanisms are needed. How can the states in Northeast Asia develop such measures, given their high level of mutual distrust? Should confidence-building measures come first, or does confidence-building depend on prior trust-building? This paper explores insights from the academic literature on trust, highlighting the role of trust entrepreneurs, who are willing to open their minds to the possibility of new relationships. Five steps are identified which can lead away from mistrust. The first is to replace enemy images with a recognition of a shared security dilemma. The second is to signal a willingness for change. The third is to persist even when signals are not returned. The fourth is to enter dialogue. The fifth is to pursue steps that embed further cooperation. This approach is applied to confidence-building, trust-building, and security building in Northeast Asia. A pathway forward is sketched, starting with confidence building between the two Koreas, leading on to a peace treaty, a nuclear weapon free zone, and co-operative security arrangements in the region.